Strategi Pengelolaan MI Unggulan: Analisis Evaluatif dalam Menyusun Perencanaan Strategik MI Unggulan - Imron Arifin (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The movement on building excellent schools has developed recently. Madrasah Ibtidaiyah (Islamic Elementary Schools, MI), which used to be managed traditionally, has also been developed to that direction. The criteria of excellent education are based on the academic quality and the goals of MI. The excellent MI is indicated by the effectiveness of managing the invisible conceptual principles such as values, philosophy, and ideology. Such an effectiveness can trigger the support of the internal and external community of MI. This becomes the key of the success in managing the visible symbols and expressions like conceptual, material, and behavior manifestation. In addition, excellent MI is also indicated by its vision about the future through the strategic planning refering to self-management.